How do you differentiate g(x) = x^3sqrt(2x+1) using the product rule? Calculus Basic Differentiation Rules Product Rule 1 Answer James May 15, 2018 g'(x)=x^3/[sqrt(2x+1)]+3x^2*sqrt(2x+1) Explanation: show below: g(x) = x^3sqrt(2x+1) g'(x)=x^3*2/[2sqrt(2x+1)]+sqrt(2x+1)*3x^2 g'(x)=x^3/[sqrt(2x+1)]+3x^2*sqrt(2x+1) Answer link Related questions What is the Product Rule for derivatives? How do you apply the product rule repeatedly to find the derivative of f(x) = (x - 3)(2 - 3x)(5 - x) ? How do you use the product rule to find the derivative of y=x^2*sin(x) ? How do you use the product rule to differentiate y=cos(x)*sin(x) ? How do you apply the product rule repeatedly to find the derivative of f(x) = (x^4 +x)*e^x*tan(x) ? How do you use the product rule to find the derivative of y=(x^3+2x)*e^x ? How do you use the product rule to find the derivative of y=sqrt(x)*cos(x) ? How do you use the product rule to find the derivative of y=(1/x^2-3/x^4)*(x+5x^3) ? How do you use the product rule to find the derivative of y=sqrt(x)*e^x ? How do you use the product rule to find the derivative of y=x*ln(x) ? See all questions in Product Rule Impact of this question 1545 views around the world You can reuse this answer Creative Commons License